Managing potential interactions of subsurface resources. (February 2018) - Field, B; Barton, B; Funnell, R; Higgs, K; Nicol, A; Seebeck, H
Subsurface resources include oil, gas, coal, groundwater, saline aquifer minerals, and heat (for geothermal use). Pore space itself should also be considered as a resource as it can be used for injection of waste fluids, produced water, storage of natural gas, compressed air, and supercritical CO2 . Use of subsurface resources can overlap in space, and pressure changes at one site can remotely influence resource use at other sites. Resource use can also vary in time, such as the use of depleted oil or gas fields for natural gas or CO2 storage. Before allocation of a subsurface resource it is therefore useful to understand the potentially wide range of resources available in an area, how they might be developed successively, and how they could affect each other if used concurrently. While these issues are primarily geological, they have critical significance for legal, environmental, and economic considerations.